Investigation of a Class J - tuned Doherty amplifier - Esteves, Bryan Edward P.
The continuous development of wireless communications standards has imposed an increasing demand for flexibility of communications hardware. This demand has been largely met through advances in Software-Defined Radio (SDR) technology, facilitating high levels of transceiver re-configurability. However, such advances are often limited by the capabilities of the front-end components such as the Power Amplifier (PA) [1]. This work studied the potential enhancement of the multichannel performance of power amplifiers through the design of a Doherty Power Amplifier (OPA) using Class J - tuned carrier and peaking amplifiers. The primary goal was to properly combine two Class J amplifiers to exploit its wideband capability and observe the Doherty efficiency enhancement by analyzing the critical factors that may limit the performance of the architecture. Simulations show that the design was able to facilitate output power at the 12-W level with efficiency approaching 70% within 1.4 GHz to 2.4 GHz (>50% fractional bandwidth), PAE reaching 50% at 5-dB back off and up to 7% PAE Improvement at 10-dB back off operation. Hardware measurements show better performance from 1 GHz to 2 GHz with output power of up to 37 dBm. The study of the design considerations is able to give insight on the load modulation process at a wide band of operation. Further insights on the hardware limitations in realizing DPAs not only tuned using Class J carrier and peaking amplifiers, but also for wide band amplifiers in general are presented.